Role of Plastic Surgery in the Management of Diabetic Foot Ulcer - Nazneen, Most Afroza; Choudhury, Mohammad Ali (TAJ: Journal of Teachers Association, 2023)
This article introduces plastic surgeons' various roles in managing diabetic foot ulcers. The role of plastic surgeons is multidimensional and, of course, challenging. Sometimes, the healing process of diabetic ulcer is as simple as only adequate wound care. Sometimes, the ulcer needs reconstruction through a skin graft or flap coverage. Unfortunately, some patients need amputation or disarticulation. Again, plastic surgeons are maximizing patients' future movement ability in the case of amputation. Thus, an experienced plastic surgeon can provide an optimum lifestyle to the diabetic patient. TAJ 2022; 36: No-1: 55-61